(untitled) (KIUT Publication, 2025)
The article analyzes the information contained in the book “Rules of Khiva Architecture” by A. Boltaev, a master, painter, artist and architect who left an indelible mark on the history of Khorezm architecture, and in the manuscript of N. Golovanov, stored in the technical school. In particular, the technology of ceramic tile production, the technology of paint and varnish preparation, as well as ways of solving similar problems that they left behind were studied.